Práticas de governança de TIC e tecnologias da indústria 4.0 no apoio à gestão de TIC em cidades inteligentes brasileiras diante da pandemia COVID-19 - Costa, Jalisson Tavares (2023)
Facing a scenario of uncertainties catalyzed by the COVID-19 pandemic, the decision-making of ICT Managers in smart cities has become indispensable for the technological development of the municipality. This study analyzes the effects of ICT Governance practices and the use of Industry 4.0 technologies in the decision-making of ICT managers in Brazilian cities considered smart in the face of the COVID-19 pandemic. To this end, 39 municipalities were selected based on rankings of Brazilian smart cities, and data was collected through the Brazilian electronic system of citizen service (e-SIC) and survey application with ICT Managers. Of the results achieved, we highlight the use of ITIL and PDTIC as the most used ICT Governance practices and the use of Business Intelligence and Cloud Computing as technological resources of Industry 4.0. In addition, the need to develop a planning culture and the need for internal training of professionals in the face of new technological resources was verified. It was evidenced that both ICT governance practices and the use of Industry 4.0 technologies have positive effects if used holistically following the strategic objectives of the municipality. The senior management of municipalities must see the importance of making constant investments both in infrastructure and in the technical capacity of professionals, prevailing the efficiency and effectiveness of ICT use.